Sweetie - Miles, Ellen (Miles, Ellen. Puppy place., 2010)
Charles loves Sweetie at first sight. For such a small pup, she has a whole lot of charisma. But Buddy is jealous every time the new miniature poodle gets near the family. Can Charles find a home for this cuddly sweetheart without upsetting his own puppy?